Os sistemas internacionais de proteção aos direitos humanos e a responsabilidade do estado no enfrentamento à violência doméstica e familiar - SOUZA, Luanna Tomaz de (Centro Universitário UNIFAFIBE, 2023)
In the present article we analyze, from the performance of the international human rights protection systems, the extent of the State's responsibility in facing the violence committed against women. The purpose of the article is to verify how the global and inter-american human rights protection system has understood the state's role in situations of domestic and family violence. A feminist methodology based on the perspective of transformation of the institutions is realized, recognizing limits and also presenting potentialities in the defense and promotion of women's rights. The research is bibliographic and documentary, being analyzed the international and national documents of recognition of the rights of women and decisions of the Inter-American Court of human rights on the subject.